Ensuring food and nutrition security in rural Nigeria: An assessment of the challenges, information needs, and analytical capacity - Akinyele, Isaac O. (International Food Policy Research Institute, 2009)
Nigeria is still characterized by high reliance on food imports. Malnutrition is widespread in the entire country and rural areas are especially vulnerable to chronic food shortages, malnutrition, unbalanced nutrition, erratic food supply, poor quality foods, high food costs, and even total lack of food. This phenomenon cuts across all age groups and categories of individuals in the rural areas. There is a high level of malnutrition among children in rural Nigeria; the figures differ with geopolitical zones, with 56 percent reported in a rural area of South West and 84.3 percent in three rural communities in the northern part of Nigeria. Nationally, the overall prevalence of stunting, wasting, and underweight are 42.0 percent, 9 percent and 25 percent, respectively. The problem of food and nutrition security in Nigeria has not been adequately and critically analyzed, despite various approaches at addressing the challenge. The enormous amount of money spent in attempting to assure the food security of Nigerians without success calls for a fundamental review of the past approaches and achievements to see what lessons can be learned to re-strategize and develop an approach that will ensure that better progress is made toward achieving the first Millennium Development Goal. Since the majority of Nigerians (70 percent) live in rural areas, an analysis of the food and nutrition security status of rural dwellers will provide a clear picture of what needs to be done to assure food security in Nigeria with the attendant improvements in nutrition status when all the other necessary conditions, such as adequate health and care, are present. The main objective of this knowledge review was to collect and summarize available secondary literature on food and nutrition security in rural Nigeria. The framework for the analysis of food and nutrition security details the factors responsible for low consumption of food and resulting malnutrition. The socioeconomic and political environment at the national and subnational level is the principal determinant of food security, since it influences food availability, stability of food supplies, and access to food, which in turn influence the amount of food consumed. When these factors interact with the health and sanitation environment as well as care practices they determine the nutritional status of the individual. There is a dearth of national surveys providing datasets for the analysis of food and nutrition security in rural Nigeria. Though there have been a number of individual and institutional efforts and attempts at generating databases on food and nutrition security for Nigeria, these efforts are hampered by inadequate funds to implement large-scale surveys. Fundamentally, we find that food insecurity and malnutrition in rural areas of Nigeria result from non implementation and/or faulty implementation of the National Food and Nutrition Policy and National Plan of Action for Food and Nutrition. Other reasons identified include unacceptably high levels of poverty in rural households, low priority for nutrition on the agenda of government and resulting poor funding, poor understanding by policymakers of the content of nutrition programs in relation to other sectors, poor infant and child feeding practices, inadequate access to healthy environment and health services as well as various care practices. The review concludes that the existing knowledge of food and nutrition security in rural areas of Nigeria does not offer detailed information to the household level, at which greater understanding is required to help design interventions that will change the unacceptable food and nutrition situation of rural dwellers in Nigeria. This gap needs to be filled to make progress in changing the food and nutrition security situation of rural dwellers in Nigeria. Identified gaps in knowledge include the issue of mainstreaming nutrition considerations and activities into poverty reduction, agricultural development policies, and food security interventions. There is a need to understand and appreciate the distinctness of nutrition and prioritize its appropriate integration into all sectors and departments working on food security in Nigeria. Similarly, knowledge of the impact of seasonal variations, the environment, and livelihoods on food usage, consumption patterns, food coping strategies, and food and nutrition security status is important for action in Nigeria. The knowledge gaps also include understanding the interconnectedness of gender factors and their roles in achieving household food and nutrition security, and understanding the impact of an integrated approach such as the integration of gender, environment, nutrition and agricultural activities, in achieving livelihoods for women, household food and nutrition security. The review recommends a strategic partnership and collaboration of all stakeholders to produce datasets that will allow for new directions and a plan of action to seek a comprehensive integration of nutrition and coordination of food security interventions among all partners at all levels, particularly in government ministries and agencies. This multi-stakeholder and multidimensional approach is required for an effective mainstreaming, integration and coordination of food and nutrition activities.